2017
DOI: 10.1155/2017/4970802
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroid Torsion during Pregnancy: A Case of Laparotomic Myomectomy at 18 Weeks’ Gestation with Systematic Review of the Literature

Abstract: Uterine myomas are the most common benign growths affecting female reproductive system, occurring in 20–40% of women, whereas the incidence rate in pregnancy is estimated from 0.1 to 3.9%. The lower incidence in pregnancy is due to the association with infertility and low pregnancy rates and implantation rates after in vitro fertilization treatment. Uterine myomas, usually, are asymptomatic during pregnancy. However, occasionally, pedunculated fibroids torsion or other superimposed complications may cause acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
22
0
4
Order By: Relevance
“…However, in the presence of intractable symptoms, some patients have been offered termination of pregnancy [ 8 ]. Alternatively, both antepartum myomectomy [ 8 10 ] and caesarean myomectomy [ 11 15 ] have been done successfully in carefully selected cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of intractable symptoms, some patients have been offered termination of pregnancy [ 8 ]. Alternatively, both antepartum myomectomy [ 8 10 ] and caesarean myomectomy [ 11 15 ] have been done successfully in carefully selected cases.…”
Section: Introductionmentioning
confidence: 99%
“…Till date, the incidence or prevalence of pedunculated subserosal myoma during gestation is unknown. Available data stem from some few published case reports [14, 18–20]. The existence of a pedunculated fibroid is the primary requisite for its torsion [16].…”
Section: Discussionmentioning
confidence: 99%
“…Myoma and pregnancy have adverse effects on each other, and the most serious effect is uterine torsion. [3][4][5] A study by Huang et al 6 revealed that the occurrence of uterine torsion in the third trimester of pregnancy may be correlated with an abnormal fetal position, older maternal age, and uterine ligament relaxation.…”
Section: Causes Of Uterine Torsion During Gestationmentioning
confidence: 99%